2022
DOI: 10.3389/fpls.2022.844635
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Perspectives on Breeding for Legume–Cereal Intercrops

Abstract: Compared to sole crops, intercropping—especially of legumes and cereals—has great potential to improve crop yield and resource use efficiency, and can provide many other ecosystem services. However, the beneficial effects of intercrops are often greatly dependent on the end use as well as the specific species and genotypes being co-cultivated. In addition, intercropping imposes added complexity at different levels of the supply chain. While the need for developing crop genotypes for intercropping has long been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 79 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…Studies have shown that some legumes, such as white lupine, can develop proteoid roots or cluster roots in soils low in available P. These specialized roots improve P uptake and, through the exudation of organic acids, reduce soil pH, solubilizing P from stable P pools [47,48]. Cowpea, whether grown as a sole crop or intercropped, also appears to have the ability to access more P than other species, increasing the activities of acid and alkaline phosphatases [16,17]. Makoi et al [49] demonstrated that increasing cowpea density significantly enhanced acid and alkaline phosphatase activity, under conditions like those in this study, providing a primary explanation for the result.…”
Section: Nutrient Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that some legumes, such as white lupine, can develop proteoid roots or cluster roots in soils low in available P. These specialized roots improve P uptake and, through the exudation of organic acids, reduce soil pH, solubilizing P from stable P pools [47,48]. Cowpea, whether grown as a sole crop or intercropped, also appears to have the ability to access more P than other species, increasing the activities of acid and alkaline phosphatases [16,17]. Makoi et al [49] demonstrated that increasing cowpea density significantly enhanced acid and alkaline phosphatase activity, under conditions like those in this study, providing a primary explanation for the result.…”
Section: Nutrient Acquisitionmentioning
confidence: 99%
“…The results showed that the triticale-pea and barley-pea intercrops provided the highest grain yields and average weights of 1000 grains. Maize (Zea mays L.)-legume intercrops can also provide protein-rich food in low-input agricultural systems, bringing overall benefits to soil fertility conservation, pest management, and animal feed [16,17]. In Malawi, a three-year study was carried out to compare the performance of maize-legume intercropping under conservation agriculture and conventional tillage on twelve farms [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, intercropping traits involved in technical, quality and other downstream processes including ripening time and seed color require further optimization. Furthermore, also complementary aspects related to species synergy during the growth period, for example, “mixing ability” and “species compatibility” are equally important breeding goals that, to date, have received little attention in scientific literature ( Kiaer et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alongside this, the trend towards homogeneity has favoured a predominantly reductionist approach to modern crop breeding (e.g. Kiær et al, 2022), which assumes that the desirable traits for enhanced crop performance can be assembled in single, optimised genotypes to meet the goals of crop quantity, uniformity and consistency valued by processors and other end users. While this approach combines much functional diversity from many sources in a cultivar's pedigree and has led to highly productive modern cropping systems, the lack of diversity across scales, from crops to value chains, has created vulnerabilities in food systems that become particularly apparent during periods of external stress (Khoury et al, 2014; Mahaut et al, 2021).…”
Section: Managing Agricultural Diversity and Heterogeneitymentioning
confidence: 99%